Effects of low carbohydrate diets on weight and glycemic control among type 2 diabetes individuals: a systemic review of RCT greater than 12 weeks Efectos de las dietas bajas en carbohidratos sobre el peso y el control glicémico en individuos con diabetes tipo 2: revisión sistemática de estudios aleatorizados de más de 12 semanas - L. M. Castañeda-González; M. Bacardí Gascón; A. Jiménez Cruz (Nutrición Hospitalaria, 2011)
Introduction: Low carbohydrate diets (LCD) have shown beneficial effects on short-term weight reduction programs for obese individuals without diabetes, but the long-term evidence of efficacy on individuals with type 2 diabetes is not conclusive. Objective: To evaluate, the effectiveness of 12 or more weeks of LCD compared to Low Fat Diet (LFD), Usual Care Diet (UCD) or Low Glycemic Index Diet (LGID) on weight reduction and AIC on type 2 diabetes individuals. Methods: A systematic review was conducted on randomized trials registered in PubMed, Cochrane and EBSCOhost from January 1st 2000 to January 1st 2010 including those with an intervention program with LCD in type 2 diabetes subjects and a follow-up ≥ 12 weeks. Available data on study design; carbohydrate composition of diet; duration of diet; and the outcomes of weight, lipid levels (total, low density lipoprotein and high-density lipoprotein cholesterol, and triglycerides), hemoglobin A1C percent and/or fasting glucose were extracted. Results: Five studies showed greater weight reduction with LCD, of which four demonstrated no significant difference. The longest trial intervention studies did not show a difference in weight change. Only two studies showed greater reduction of A1C with LCD, including the longest intervention trial with a low carbohydrate Mediterranean diet. Conclusions: This review shows that there are no consistent differences in weight and A1C changes over the long-term treatment with LCD and LFD, UCD or LGID. Introducción: Las dietas bajas en carbohidratos han demostrado, a corto plazo, efectos benéficos sobre la pérdida de peso en individuos obesos sin diabetes, sin embargo la evidencia sobre su efectividad a largo plazo en individuos con diabetes tipo 2 no es concluyente. Objetivo: Evaluar el efecto de dietas bajas en carbohidratos (DBC) en intervenciones mayores a 12 semanas comparadas con dietas bajas en grasas (DBG), dietas de cuidado común (DCC) o dietas con bajo índice glicémico (DBIG), sobre la pérdida de peso y la hemoglobina glucosilada (A1C) en individuos con diabetes tipo 2. Métodos: Se realizó una revisión sistemática de estudios aleatorizados publicados en PubMed, Cochrane y EBSCOhost del 1º de Enero del 2000 al 1º de Enero del 2010. Se extrajeron datos sobre el diseño del estudio, la composición de carbohidratos de la dieta, la duración de la dieta y resultados de cambios en peso, en porcentaje de A1C, glucosa en ayuno y lípidos sanguíneos. Resultados: Cinco estudios mostraron mayor reducción de peso con DBC, de los cuales cuatro no demostraron diferencia estadística. El estudio de mayor tiempo de intervención no mostró diferencia en la pérdida de peso. Únicamente dos estudios mostraron mayor reducción en el porcentaje de A1C con DBC, incluyendo el estudio de mayor tiempo de intervención. Conclusiones: Esta revisión muestra la falta de consistencia en las diferencias sobre los cambios en el peso y la A1C en intervenciones con seguimiento mayor de 12 semanas con DBC comparadas con DBG, DCC o DBIG.